A monopoly union model of wage determination with taxes and endogenous capital stock: an empirical application to the Finnish manufacturing industry - Pasi Holm; Seppo Honkapohja; Erkki Koskela (Bank of Finland, 1990)
The paper formulates a model of wage determination in accordance with the notion of a monopoly union determining wages after which the firm decides on employment. The novelty is to incorporate investment and capital decisions by firms. In the theoretical part the subgame-perfect Nash equilibrium and its comparative statics for wages, capital stock and employment are characterized in various cases.
URN:NBN:fi:bof-201807311807
Keywords: 330